Menjaga Keseimbangan Emosional Santri: Tantangan Kesehatan Mental di Lingkungan Pondok Pesantren - Lusiana Lusiana; Ahmad Hatta; Muharam Purnama (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the urgency of maintaining emotional balance and mental health of students in Islamic boarding schools (pesantren) characterized by a strict and highly disciplined system. The high dual pressure of academic obligations and religious standards, coupled with limited personal time and social isolation, can trigger ongoing stress and anxiety in students. The purpose of this study is to comprehensively describe the mental health challenges faced by students in Islamic boarding schools and provide constructive recommendations to improve their psychological well-being. The research methodology uses a qualitative approach with a phenomenological study, where data are collected through in-depth interviews and participant observation at MA MILBoS, then analyzed using thematic analysis techniques. The discussion shows that Islamic boarding schools have developed emotional management through the synergy of the Religious Approach, the Coaching Approach, and the Professional Counseling Services already available at MILBoS. However, there are challenges in coaching due to the potential lack of clinical expertise of the mentors to handle serious mental problems. Conclusions and Implications emphasize that the mental health of students requires a holistic approach, and implementation is focused on optimizing and integrating the role of Professional Counselors with the coaching system. This is crucial to ensure that students not only excel academically and spiritually, but also possess strong emotional resilience and balance.